The Urgency of Mediation in the Religious Courts - Asep Syarifuddin Hidayat (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This article addresses the necessity of using mediation in religious courts as a means of conflict resolution because it is proven to be both effective and helpful. In the context of resolving economic disputes according to Sharia law, mediation is an essential component in the process of bringing the opposing parties together to find a solution that is equitable and conducive to peaceful coexistence. This article describes the scope of mediation in religious courts. It discusses the several types of problems that can be handled by mediation, including business, contractual, and inheritance disagreements. In addition, the concepts of mediation that have been embraced by religious courts, such as the values of liberty, volunteering, and confidentiality, are explained below. The research method that was employed was a qualitative research method that used an approach that was based on both the literature and legislative requirements. According to the findings of recent research, the use of mediation in the process of conflict resolution can result in significant time, financial, and resource savings while also contributing to the preservation of amicable relations between the disputants. This article also provides a list of various case studies and empirical evidence that support the benefits of mediation within the setting of religious courts.Keywords: Mediation; Religious courts; Dispute Abstrak:Artikel ini membahas perlunya penggunaan mediasi di pengadilan agama sebagai sarana penyelesaian konflik karena terbukti efektif dan membantu. Dalam konteks penyelesaian sengketa ekonomi menurut hukum syariah, mediasi merupakan komponen penting dalam proses mempertemukan pihak-pihak yang bertikai untuk mencari solusi yang adil dan kondusif bagi hidup berdampingan secara damai. Artikel ini memberikan gambaran tentang ruang lingkup mediasi di peradilan agama. Ini membahas beberapa jenis masalah yang dapat ditangani oleh mediasi, antara lain masalah bisnis, perselisihan kontrak, dan perselisihan warisan. Selain itu, konsep-konsep mediasi yang dianut oleh peradilan agama seperti nilai-nilai kebebasan, kerelawanan, dan kerahasiaan dijelaskan di bawah ini. Metode penelitian yang digunakan adalah metode penelitian kualitatif yang menggunakan pendekatan yang didasarkan pada literatur dan persyaratan peraturan perundang-undangan. Menurut temuan penelitian terbaru, penggunaan mediasi dalam proses penyelesaian konflik dapat menghasilkan penghematan waktu, keuangan, dan sumber daya yang signifikan sementara juga berkontribusi pada pelestarian hubungan damai antara pihak yang berselisih. Artikel ini juga memberikan daftar berbagai studi kasus dan bukti empiris yang mendukung manfaat mediasi dalam lingkungan peradilan agama.Kata Kunci: Mediasi; Pengadilan Agama; Sengketa